Riboswitch theo/mete as a transcription regulation tool for xanthomonas citri subsp. Citri - Bueno, Danilo [UNESP] (2021)
Xanthomonas citri subsp. citri (X. citri) is the causal agent of Asiatic Citrus Canker (ACC), a disease that affects citrus. ACC has no cure, and growers must rely on special agricultural practices to prevent bacterial spreading. Understanding X. citri basic biology is essential to foresee potential genetic targets to control ACC. Traditionally, microbial genetics use gene deletion/disruption to investigate gene function. However, essential genes are difficult to study this way. Techniques based on small-RNAs and antisense-RNAs are powerful for gene characterization, but not yet fully explored in prokaryotes. One alternative is riboswitches, which derive from bacteria, and can control transcription/translation. Riboswitches are non-coding RNAs able to modulate gene expression in the presence of specific ligands. Here we demonstrate that the riboswitch theo/metE decreases parB expression in X. citri in a platform responsive to theophylline. By monitoring cell respiration, we showed that higher concentrations of the ligand interfered with bacterial viability. Therefore, we determined the safe dose of theophylline to be used with X. citri. Finally, in downstream investigations of parB transcription modulation, we show evidence for the fact that ParB is stable, remains functional throughout the cell cycle, and is inherited by the daughter cells upon cell division.